EFFECT OF NONI FRUIT EXTRACT ON THE INTERNAL QUALITY, FOAM INDEX, AND HAUGH UNIT OF THE CHICKEN EGGS - Natalius Abi; Charles Venirius Lisnahan; Theresia Ika Purwatiningsih (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2021)
This study aimed to determine the effect of noni fruit extract on the internal quality, foam index, and haugh unit of layers eggs. This research has been carried out at the Chemistry Laboratory of Widya Mandira University Kupang, and the Laboratory of the Faculty of Agriculture, University of Timor, Kefamenanu during February 12, until March 25, 2020. This study used eggs of layer chicken, each treatment using 25 eggs. The method used was a completely randomized design with a one-way pattern consisting of 5 treatments and 5 replications. The treatments given were T0 (control), T1 (2 ml noni fruit extract), T2 (4 ml noni fruit extract), T3 (6 ml noni fruit extract), and T4 (ampicillin). The variables observed were egg weight, air sac diameter, albumen height, egg yolk index, foam leakage, foam index, and Haugh unit. The results of statistical analysis showed the effect of noni fruit extract on egg weight, air sac diameter, foam leakage, foam index, and Haugh unit value. The mean value of each variable showed that the 6 ml (T3) noni extract treatment was better than the other treatments (T0, T1, T2, and T4). It was concluded that to maintain egg quality for up to 21 days, could be preserved with a concentration of 6% noni fruit extract.